Estimated rates of recurrence, cure, and treatment abandonment in patients with pulmonary tuberculosis treated with a four-drug fixed-dose combination regimen at a tertiary health care facility in the city of Rio de Janeiro, Brazil - Silva,Vangie Dias da (2017)
ABSTRACT Objective: To estimate the rates of recurrence, cure, and treatment abandonment in patients with pulmonary tuberculosis treated with a four-drug fixed-dose combination (FDC) regimen, as well as to evaluate possible associated factors. Methods: This was a retrospective observational study involving 208 patients with a confirmed diagnosis of pulmonary tuberculosis enrolled in the Hospital Tuberculosis Control Program at the Institute for Thoracic Diseases, located in the city of Rio de Janeiro, Brazil. Between January of 2007 and October of 2010, the patients were treated with the rifampin-isoniazid-pyrazinamide (RHZ) regimen, whereas, between November of 2010 and June of 2013, the patients were treated with the rifampin-isoniazid-pyrazinamide-ethambutol FDC (RHZE/FDC) regimen. Data regarding tuberculosis recurrence and mortality in the patients studied were retrieved from the Brazilian Case Registry Database and the Brazilian Mortality Database, respectively. The follow-up period comprised two years after treatment completion. Results: The rates of cure, treatment abandonment, and death were 90.4%, 4.8%, and 4.8%, respectively. There were 7 cases of recurrence during the follow-up period. No significant differences in the recurrence rate were found between the RHZ and RHZE/FDC regimen groups (p = 0.13). We identified no factors associated with the occurrence of recurrence; nor were there any statistically significant differences between the treatment groups regarding adverse effects or rates of cure, treatment abandonment, or death. Conclusions: The adoption of the RHZE/FDC regimen produced no statistically significant differences in the rates of recurrence, cure, or treatment abandonment; nor did it have any effect on the occurrence of adverse effects, in comparison with the use of the RHZ regimen.